1982
DOI: 10.1073/pnas.79.21.6569
|View full text |Cite
|
Sign up to set email alerts
|

Taxol-induced anaphase reversal: evidence that elongating microtubules can exert a pushing force in living cells.

Abstract: The effects of taxol on mitosis in Haemanthus endosperm were studied. Immuno-gold staining was used to visualize microtubules; observations on microtubule arrangements were correlated with studies in vivo. Mitosis is slowed down, but not arrested, by taxol over a wide range of concentrations. Taxol promotes the formation ofabundant new microtubules and lateral association within and between microtubule arrays (spindle fibers). This leads to a pronounced reorganization of the spindle, especially at the polar re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
1

Year Published

1984
1984
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 23 publications
4
33
1
Order By: Relevance
“…It has indeed been observed that in anaphase, all the chromosomes move at a velocity independent of size, indicating that their displacement is not limited by their hydrodynamic properties. Also, this displacement is inhibited if the depolymerization is blocked by taxol (17). This is consistent with our model in which slowing down depolymerization results in slowing particle displacement.…”
Section: Two Observations With Which the Model Is Consistentsupporting
confidence: 79%
“…It has indeed been observed that in anaphase, all the chromosomes move at a velocity independent of size, indicating that their displacement is not limited by their hydrodynamic properties. Also, this displacement is inhibited if the depolymerization is blocked by taxol (17). This is consistent with our model in which slowing down depolymerization results in slowing particle displacement.…”
Section: Two Observations With Which the Model Is Consistentsupporting
confidence: 79%
“…The primary effects included aberrant spindle formation and extra microtubule arrays in prometaphase, a heavier packing of microtubules (visualized as a more uniform staining of tubulin), and a widening of the spindle midzone and premature clearing of microtubules from the future cell plate at anaphase (as if a phragmoplast were beginning to form at anaphase). These also were the primary effects of taxol noted by Bajer and colleagues in Haemanthus (Bajer et al, 1982;Molè-Bajer and Bajer, 1983). A noteworthy difference is that we observed more pronounced effects at prometaphase than did the previous authors.…”
Section: Neocentromeres Are Insensitive To Perturbations In Microtubucontrasting
confidence: 55%
“…Taxol treatments sufficient to induce gross alterations in spindle architecture caused no apparent reduction in the extent or number of neocentromeres ( Figures 5B and 5E, Table 1), suggesting that microtubule dynamics contribute little to neocentromere motility. A slight enhancing effect of taxol on neocentromere activity (Tables 1 and 2) can be explained if taxol impairs kinetochore-mediated movement (Bajer et al, 1982;Waters et al, 1996) but has no effect on neocentromere movement. The fact that neocentromeres are pronounced on the most disturbed spindles supports the view espoused previously (Yu et al, 1997) that Ab10 provides or recruits proteins to neocentromeres that generate their movement de novo.…”
Section: Mechanism Of Neocentromere Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Among the numerous microtubular poisons, taxol (25,26) possesses the unique property of stabilizing microtubules both in vivo (27,28) and in vitro (29). The effects of taxol are widespread among eukaryotic cells, including mammalian cells (27,28,30,31), Xenopus eggs (32), sea urchin eggs (33), Haemanthus endosperm (34), Trypanosoma (35), Plasmodium (unpublished results), and Physarum amoebae (36,37). In order to compare the interaction of taxol on tubulin from two distinct evolutionary lines of eukaryotic cells, we have studied the effects of various taxol derivatives, in particular baccatine III ( Fig.…”
mentioning
confidence: 99%